Effect of Nitric Acid on the Low Fluorescing Performance of Drilling Fluid Lubricant Based Animal and Vegetable Oils. (2nd December 2013) - Zhou, Feng-shan; Xiong, Zheng-qiang; Cui, Bao-lin; Liu, Feng-bao; Li, Guang-huan; Wei, Jin-ran; Cui, Hua
Abstract : After synthesis of mixed fatty acid triethanolamine ester surfactant based on animal and vegetable mixed oils, the reaction solution was added into 4% (wt/wt) liquid nitric acid or 9% (wt/wt) solid nitric acid as eliminating fluorescent agent continuing to react from 1 to 2 hours. The low fluorescence lubricant named E167 for drilling fluid was prepared, in which maximum fluorescence intensity (F m a x ) was less than 10 in three-dimensional fluorescence spectra of excitation wavelength range. When the E167 was added into fresh water based drilling fluid at the dosage of 0.5% (wt/wt), the sticking coefficient reduced rate (Δ K f ) is 78% and the extreme pressure (E-P) friction coefficient reduced rate (Δ f ) is 79%. In the case of 4% brine mud with 0.5% (wt/wt) E167 in it, the Δ K f and Δ f are 75% and 62%, respectively. After the hot rolling ageing test 180°C × 16 h with the E167 was added into fresh water based drilling fluid at the dosage of 1% (wt/wt), the Δ K f and Δ f are greater than 70%, which shows a much better lubrication properties of strong resistance to high temperature. The fresh water based drilling fluid which contains 1% (wt/wt) E167 is almost nonfoaming even after hot rolling ageing 120°C × 16 h.